Upaya Mereduksi Prokrastinasi Akademik Melalui Konseling Kelompok dengan Pendekatan Behavioristik Pada Siswa SMK - Puswanti Puswanti (PSIKOPEDAGOGIA Jurnal Bimbingan dan Konseling, 2014)
This study aims to determine the effectiveness of group counseling with a behavioristic approach to reducing academic procrastination on vocational students. This type of research is classroom action research, consisting of two cycles and each cycle consisting of three acts. Each cycle begins with the planning, implementation, observation, and reflection. The research subject was determined by purposive sampling of six students with high academic procrastination level criteria. The research instrument used in the form of academic procrastination scale and guidelines for observation. Data analysis using t-test formula. The results showed that the average student academic procrastination 107.33 pretest and posttest mean of 66.5 and 100% of the students are in the category of academic procrastination low after getting action. It can be concluded that the counseling group with the approach used to reduce the effective behavioristic academic procrastination, vocational students. The results of this study useful for counselors to help students reduce academic procrastination through a counseling group with the behavioristic approach.